Identification of Javan Hawk-Eagle (Nisaetus bartelsi) and Its Habitat on the Island of Bali - Widiyavedanta, Gde Oka; Syartinilia; Aryati Mulyani , Yeni (Media Konservasi, 2025)
The Javan Hawk-Eagle (Nisaetus bartelsi), an endemic species of Java, has been occasionally observed in Bali, prompting the need for scientific verification due to its critical conservation status. This study aimed to confirm the presence of the Javan Hawk-Eagle in Bali and map its potential distribution based on habitat suitability using an integrated spatial-ecological approach. A probability distribution model was developed using logistic regression with NDVI (Normalized Difference Vegetation Index), slope, and elevation as predictor variables. The resulting probability map was subsequently delineated using land cover, land use data, and information obtained directly from key informant interviews to produce a refined predicted suitable habitat patches map for the Javan hawk-eagle. To confirm its reliability, we conducted patch occupancy surveys to confirm the Javan Hawk-Eagles existence in patches that have historical occurrence of Javan Hawk-Eagle. Logistic regression modeling identified the Javan Hawk-Eagle's potential distribution area of 1,069.4 km². Using this model and information from key informants, forest function maps, and land cover maps, 14 predicted habitat patches were delineated. Subsequent patch occupancy surveys confirmed three of these patches as actual habitats for the Javan Hawk-Eagle on Bali, namely West Bali Protected Forest, Batukaru and Batukahu Area, and Buyan-Tamblingan Lake Tourism Forest. These findings provide the first empirically validated confirmation of the Javan Hawk-Eagle’s presence in Bali, supported by direct photographed observations verified by experts, and delineate key habitat patches for future conservation planning.